Comparison of Single-Level Open and Minimally Invasive Transforaminal Lumbar Interbody Fusions Presenting a Learning Curve. (25th January 2020) - Kovari, Viktor Zs.; Kuti, Akos; Konya, Krisztina; Szel, Istvan; Szekely, Anna K.; Szalay, Krisztian
Abstract : Background . Comparison of single-level open and minimally invasive transforaminal lumbar interbody fusions (O-TLIF and MI-TLIF) of a single surgeon and presentation of his MI-TLIF learning curve in a retrospective observational cohort study. Methods . 27 MI-TLIF and 31 O-TLIF patients, performed between 03/01/2013 and 03/31/2018, were compared regarding the operative time, blood loss, blood transfusion frequency, postoperative length of stay (LOS), and adverse events. An overall comparison of pre- and postoperative Oswestry Disability Index (ODI) results and Visual Analog Score (VAS) results of low back and leg pain was performed in the case of the two techniques. For a learning curve presentation, the MI-TLIF cases were compared and the optimal operative time was determined. Results . The gender ratio and age did not differ in the groups. Operative time showed no difference (P = 0.88 ) between the MI-TLIF (161.2 ± 33.7 minutes) and O-TLIF groups (160 ± 33.6 minutes). Intraoperative blood loss was less (P ≤ 0.001 ) in the MI-TLIF group (288.9 ± 339.8 mL) than in the O-TLIF group (682.3 ± 465.4 mL) while the incidence of blood transfusion was similar (P = 0.64 ). The MI-TLIF group had shorter LOS (2.7 ± 1.1 days vs. 5 ± 2.7, P ≤ 0.001 ). The frequencies of the surgical site infections (SSI), durotomy, new motor, and sensory deficit were not significantly different (P = 0.17, 0.5, 0.29, 0.92). All the ODI, the VAS low back pain, and the VAS leg pain scores improved in both groups significantly (P ≤ 0.001, P ≤ 0.001, and P ≤ 0.001 in the MI-TLIF group and P ≤ 0.001, P ≤ 0.001, and P ≤ 0.001 in the O-TLIF group). The comparison of the pre- and postoperative results of the ODI and VAS questionnaires of the two techniques showed no significant difference regarding the improvement of these scores (MI-TLIF versus O-TLIF pre- and postoperative ODI difference p = 0.64, VAS low back pain P = 0.47, and VAS leg pain P = 0.21 ). Assessing the MI-TLIF learning curve, operative time was shortened by 63 minutes (P = 0.04 ). After the 14th MI-TLIF case, the surgical duration became relatively constant. Comparing the 14th and previous MI-TLIF cases to the later cases, LOS showed reduction by 1.03 days (P = 0.01 ), while the other parameters did not show significant changes. Conclusions . Similar operative time and postoperative quality of life improvement can be achieved by MI-TLIF procedure as with O-TLIF, and additionally LOS and blood loss can be reduced. When comparing parameters, MI-TLIF can be an alternative option for O-TLIF with a similar complication profile. The learning curve of MI-TLIF can be steep, although it depends on the circumstances.